Natural association of the entomopathogenic fungi Aschersonia placenta with spiralling whitefly (Aleurodicus dugesii) in Bali, Indonesia - I PUTU SUDIARTA; I PUTU WIRYA SUPUTRA; NI PUTU MERTANINGSIH; GUSTI NGURAH ALIT SUSANTA WIRYA; DEWA GEDE WIRYANGGA SELANGGA; I WAYAN EKA KARYA UTAMA; I WAYAN DIKSA GARGITA; KATRINA KLETT; I KADEK WISMA YUDHA (Society for Indonesian Biodiversity, 2024)
Abstract. Sudiarta IP, Suputra IPW, Mertaningsih NP, Wirya GNAS, Selangga DGW, Utama IWEK, Gargita IWD, Klett K, Yudha IKW. 2024. Natural association of the entomopathogenic fungi Aschersonia placenta with spiralling whitefly (Aleurodicus dugesii) in Bali, Indonesia. Biodiversitas 25: 4067-4073. The whitefly is one of the most common pests in agriculture, and one highly polyphagous species is the spiral whitefly (Aleurodicus sp.). The fungal genus Aschersonia can be used to control Aleurodicus sp.. This research has potential applications in agriculture because it can produce a new environmentally friendly method to control whitefly infestations. The aim of this study was to analyze the morphology and molecular characteristics of Aschersonia and their hosts in Bali. The samples were taken from several areas in Bali Province. Morphological identification was carried out at the Plant Pathology Laboratory, Faculty of Agriculture, Universitas Udayana. The conidia of Aschersonia were fusoid with tapered ends, 9-16 ?m long and 1.5-2 ?m wide, and the color of the culture was white to yellowish white. Molecular analysis exhibited that DNA bands measuring between 500-600 bp were successfully amplified with universal primers ITS1/ITS4. Aschersonia infected spiralling whiteflies has never been reported in mulberry plants. Further phylogenetic analysis showed that Aschersonia-infected spiralling whiteflies were in the same group as Aschersonia placenta/ Hypocrella raciborskii isolates from Thailand and India. Aleurodicus dugesii Cockerell 1896 had morphological characteristics, such as vasiform orifice with lingula extending beyond the borders of orifice, compound pores present on puparia, and thoracic legs with claws. The results of morphological analysis showed that A. dugesii from Bali (LC491422) had the closest kinship to A. dugesii from the USA (AY521251). This is the first report of the identification of Aschersonia placenta associated with A. dugesii in Indonesia.